Treatment With Lipopolysaccharide Induces Distinct Changes in Metabolite Profile and Body Weight in 129Sv and Bl6 Mouse Strains - Piirsalu, Maria; Taalberg, Egon; Lilleväli, Kersti; Tian, Li; Zilmer, Mihkel; Vasar, Eero (Frontiers in Pharmacology, 2020)
Mouse strains differ significantly in their behaviors and responses to pathogenic and pharmacological agents. This study seeks to characterize behavioral and metabolomic profiles of two widely used mouse lines, 129S6/SvEvTac (129Sv) and C57BL/6NTac (Bl6), to acute administration of lipopolysaccharide (LPS). LPS caused a significant suppression of locomotor activity and a decline in body weight (BW) in both strains within 24 h. However, the BW loss was more pronounced in Bl6 than in 129Sv. Comparison of strains revealed clear differences between their metabolomic profiles. According to the general linear model analysis (GLM), the 1.5 h LPS challenge in Bl6 caused a decrease of propionylcarnitine (C3), glucogenic amino acids, and acetylornithine (Ac-Orn), whereas the response of 129Sv included decreased concentrations of short-chain acylcarnitines (SCACs), citrulline, and elevation of glycerophospholipid (PCaa C42:0) and sphingolipid [SM(OH)C16:1]. 24 h after LPS administration, robust alterations in lipid profile were observed in both strains. LPS treatment caused elevation of sphingolipids, phosphatidylcholine diacyls (PCaa) as well as a decrease in lysophosphatidylcholines (LysoPC). However, the number of elevated PCaa and sphingolipids was considerably higher in 129Sv. In addition to lipids, 24 h LPS challenge in Bl6 mice induced increased levels of kynurenine (KYN), putrescine and decreased levels of citrulline, hexoses, Ac-Orn, and PC acyl-alkyl (PCae 38:2) as well as severe BW loss. In contrast, the 24 h LPS challenge in 129Sv mice induced increased levels of KYN, long-chain acylcarnitines (LCACs) and decreased levels of citrulline as well as moderate BW loss. Altogether, our study revealed both similarities and differences in response to LPS in Bl6 and 129Sv strains. For major differences, Bl6 mice showed stronger reduction of BW 24 h after LPS treatment, accompanied by significantly reduced levels of hexoses, the ratio between LysoPC16:1/LysoPC16:0, and elevated levels of neuroprotective putrescine. In 129Sv mice, the BW loss was milder, accompanied by increased levels of hydroxylated LCACs, probably reflecting shifts in oxidative metabolism of fatty acids. One may suggest that LPS caused stronger hypometabolic state in the Bl6 mice than in the 129Sv strain. Altogether, this study confirms that Bl6 and 129Sv mice display vastly distinct adaptation capacities independent from the nature of stressful challenge.